(untitled) (Fiep Bulletin - online, 2016)
Objective: To evaluate the profile of publications on labor and occupational hazards. Method: This research based on the Integrative Literature Review method, and the Virtual Health Library, from Medical Subject Headings work and occupational hazards, used associates. From initially identified productions and the significant number, were defined inclusion criteria. After the adjustment to them, only 11 articles to compose the final sample. Results: It found that the subject arouses the interest of researchers; especially the Portuguese and which involve more specifically the work of nursing. However, the themes discussed were approaches to professional practice in the identification and prevention of occupational hazards, occupational hazards present in the workplace, and effects from exposure to occupational hazards. Conclusion: Although there are few approaches that lead the association between work and occupational hazards, requiring further research.